Balloon‐Facilitated Delivery of a Left Ventricular Pacing Lead. Issue 2 (28th January 2011) - ELAYI, CLAUDE S.; WHITBECK, MATTHEW G.; MORALES, GUSTAVO; GURLEY, JOHN C.
<x xml:space="preserve">Abstract</x> While modern implant tools have contributed greatly to the success of cardiac resynchronization therapy, technical challenges remain. A common problem is the inability to advance left ventricular pacing leads into branch veins that are tortuous or arise at steep angles. In these cases, advancement of the lead causes it to buckle and prolapse into the coronary sinus or great cardiac vein. Lead prolapsed can be avoided by employing a balloon to temporarily obstruct the coronary sinus or great cardiac vein just upstream from the branch vein. The balloon redirects the force of advancement laterally into the branch vein, facilitating delivery. (PACE 2013; 36:e31–e34)